2021
DOI: 10.1177/0972262921989877
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence, Personality Variables and Career Adaptability: A Systematic Review and Meta-analysis

Abstract: This study conducted a systematic review and meta-analysis to examine the relationship between emotional intelligence, personality variables (Big V personality traits, self-esteem, self-efficacy, optimism and proactive personality) and career adaptability of students. Data were coded on CMA software version 3.0. Product–moment correlation coefficient (r) was considered as the effect size measure for this study. Publication bias was assessed using Egger’s regression test along with Orwin’s fail-safe N, but no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
2
12
0
3
Order By: Relevance
“…Therefore nurse managers with high emotional intelligence are known to be task-achievable managers as compared to those who do not consider their emotions in addition to their leadership fashions. Moreover, (29) found a considerable correlation between nurse managers' emotional intelligence and their different styles of leading subordinates and the findings associated well with to present study. Further, a similar report to this present findings had been documented in a cross-sectional study by (30) indicating nurse managers with high to very high emotional intelligence correlated well with their leadership styles.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore nurse managers with high emotional intelligence are known to be task-achievable managers as compared to those who do not consider their emotions in addition to their leadership fashions. Moreover, (29) found a considerable correlation between nurse managers' emotional intelligence and their different styles of leading subordinates and the findings associated well with to present study. Further, a similar report to this present findings had been documented in a cross-sectional study by (30) indicating nurse managers with high to very high emotional intelligence correlated well with their leadership styles.…”
Section: Discussionsupporting
confidence: 91%
“…First, our study adds to previous researches conducted in other industries that suggest emotional intelligence is a critical factor in employees’ career success. Numerous researchers found that people with high emotional intelligence were devoted to their career aspirations, had greater career decisions and self‐efficacy, were highly adaptive to career outcomes, and had higher job competency and employability, which in turn contributed to high career success (Hamzah et al., 2021; Parmentier et al., 2019; Priyadarshini, 2022; Sharma & Tiwari, 2022b; Tagiya et al., 2020; Vashisht et al., 2021). Hence, these findings can be applied to other industries facing similar work environment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lack of assertiveness and passivity are two common effects of low self-esteem that cause employees to accept too many tasks or tasks that they cannot manage, which increases stress ( 14 ). In this sense, it has been shown that improving self-esteem can transform threatening changes into challenges ( 15 ). Therefore, based on the results found, and in view of the current need to train in personal competencies and skills necessary for proper professional performance ( 1 , 10 ) and promotion of effective healthcare leaders ( 13 ), the relationship between global self-esteem and stress management, adaptability and mood factors of emotional intelligence is underlined.…”
Section: Discussionmentioning
confidence: 99%